Diseño y puesta en funcionamiento de un SIG como herramienta para el estudio del turismo y su planificación en las regiones del archipiélago de Las Canarreos y Cienfuegos-Trinidad-Topes de Collantes, Cuba - Quintela Fernández, J.; Remond Noa, R.; Durán Gregorio, M. E. (Geographicalia, 2016)
Today, geographic information systems are being used as a platform for managing hugh volumes of information related to the decision making process withing different fields. Given the great variety of touristic resources that Cuba has, different systems have been generated at the Faculty of Geography of the University of Havana, oriented to tourism plainning and study. In this article, two of those results are presented involving different territories: Los Canarreos Archipielago and Cienfuegos -Trinidad - Topes de Collantes region.
Keywords: Geographic Information Systems; thematic layers; spatial data